USA Policy in Sub-Saharan Africa - URNOV Andrey Yrievich (Ученые записки Института Африки Российской академии наук)
The article is devoted to Biden Administration Policy in Sub-Saharan Africa during the first half of 2022. This policy is carried out in accordance with a keynote speech “The United States and Africa: Building a 21st Century Partnership” made by Secretary of State Antony Blinken on November 17, 2021 in Abuja, Nigeria. The Secretary identified five spheres of common interest and cooperation – global health, the climate crisis, more stable and inclusive economy, defense of democracy, peace and security. The United States acknowledge a growing role of Africa in the world affairs and use all means at their disposal to preserve and strengthen their positions on the continent. The US “right” to be a global leader remains indisputable. The main enemies, as everywhere, are “authoritarian” China and Russia. The author reviews the US positions and activities in regard to conflict situations in Ethiopia, Mali, Somalia, Democratic Republic of Congo and South Sudan. The meetings and contacts are traced between A. Blinken, his deputies and assistants and African leaders – Chairpersons of African Union and AU Commission, presidents of Angola, Chad, Equatorial Guinea, The Gambia, Malawi, Somalia, Zambia, prime minister of Cote d’Ivoire, foreign ministers of South Africa, Kenia, Nigeria and other countries. The trips of two American delegations are described. One, led by Deputy Secretary of State W. Sherman to South Africa, Angola and Togo (May). The other – “the Department of State economic diplomacy delegation” to Nigeria, Kenia, South Africa and Namibia (February). Some statistics on US – Sub-Saharan Africa trade and investments are provided. The official position concerning the tasks facing Africom is cited.